2017
DOI: 10.1007/s00402-017-2738-3
|View full text |Cite
|
Sign up to set email alerts
|

High non-anatomic tunnel position rates in ACL reconstruction failure using both transtibial and anteromedial tunnel drilling techniques

Abstract: Considerable rates of non-anatomic femoral and tibial tunnel positions were found in ACL revisions with both transtibial and anteromedial femoral drilling techniques. Despite the potential of placing tunnels more anatomically using an additional AM portal, this technique does not ensure anatomic tunnel positioning. Consequently, the data highlight the importance of anatomic tunnel positioning in primary ACL reconstruction, regardless of the applied drilling technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 36 publications
0
40
0
2
Order By: Relevance
“…At the same time, current research is underlining that early ACLR improves the outcome after meniscal repair in conjunction with ACLR while protecting the knee from secondary injury like chondral lesions and aggravated meniscal lesions [1,2,34]. While osseous factors like tunnel positioning and tibial slope are established important factors for ACL graft failure, the role of periarticular structures, meniscal kinematics and strength deficits following ACLR is still a major focus of current research [6,[35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, current research is underlining that early ACLR improves the outcome after meniscal repair in conjunction with ACLR while protecting the knee from secondary injury like chondral lesions and aggravated meniscal lesions [1,2,34]. While osseous factors like tunnel positioning and tibial slope are established important factors for ACL graft failure, the role of periarticular structures, meniscal kinematics and strength deficits following ACLR is still a major focus of current research [6,[35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…TT transtibial, TP Transportal, OI Outside-In, cOI Central Outside-In, amOI AM Outside-in, CENTRAL (TP + cOI). * P > 0.005 fibers in the ACL: direct and indirect [22]. In 2012, a histological study [23] pointed to a microscopic fourlayer structure in both the direct femoral and tibial insertion, demonstrating that the direct fibers are stronger and biomechanically more important, located in the lateral femoral intercondylar ridge.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, about 54.17% (39/72) included patients had non-anatomical femoral tunnel position. Jaecker et al [36] analyzed 101 cases of ACLR failure and found 37 (36.6%) used AM technique. There were 73% non-anatomical femoral tunnel positions and 35.1% non-anatomical tibial tunnel positions in those patients with AM drilling techniques.…”
Section: Discussionmentioning
confidence: 99%